Pengaruh Laju Molar Mn Larutan Terhadap Mikrostruktur Lapisan Tipis GaN:Mn yang Dideposisi di atas Substrat Si Menggunakan Metode Sol-Gel - Sutanto, Heri; Hidayanto, Eko; Nurhasanah, Iis; Istadi, Istadi (BERKALA FISIKA, 2011)
A thin layer of material deposition of GaN: Mn by sol-gel method has done using spin-coating technique. Solution of gallium-citrate-amine maganese-Ga2O3 synthesized using as a source of Ga and Mn MnO2 as the source. Solution varied with the mole fraction solution of 60-80% Mn. Brown crystals that formed subsequently dissolved in ethylenediamine to form a gel. Subsequent gel superimposed on top of Si substrates with a spin-coater at a rate of 1100 rpm. Layers formed at temperatures of 900oC and then disintering in UHP N 2 gas environment to form the decomposition of GaN: Mn. The results of spectral analysis of energy dispersive X-ray (EDX) showed incorporation of Mn into the GaN mole fraction increased with the addition of a solution of Mn in the solution used. EDX Test results show that thin films of GaN: Mn impurity contained carbon (C) up to 36.71%. Image scanning electron microscopy (SEM) a thin layer of GaN: Mn shows in general have been obtained surface roughness (rms) morphology of the layer reaches the order of nanometers up to 24.36 nm. From the results already obtained show that the sol-gel deposition method has been able to produce a thin layer of magnetic semiconductors with a nearly homogeneous surface morphology. Thus the sol-gel method could be developed for alternative methods of deposition of thin layers that are economical and simple. Key words: GaN: Mn, CSD, Thin Layer, Mn incorporation.